Increasing Customer Loyalty Through Optimizing Customer Satisfaction With Customer Relationship Management And Company Image Strategies (Study on PT PLN (Persero) UP3 Serpong Customers) - Marsanta, Viny; Soliha, Euis (Jurnal Ilmiah Ekonomi Islam, 2024)
This study investigates the influence of Customer Relationship Management (CRM) and corporate image on customer satisfaction and loyalty in PT PLN (Persero) UP3 Serpong. Using a quantitative approach, data were collected from 213 respondents via structured questionnaires. The study employed regression analysis and Sobel tests for mediation effects. Results reveal that CRM and corporate image significantly impact customer satisfaction, which in turn mediates their effects on customer loyalty. Practical implications include strategic recommendations for PT PLN to enhance service quality and strengthen its corporate image to improve customer loyalty. The findings contribute to both managerial strategies and academic literature on customer loyalty in the electricity service industry.In addition to exploring direct effects, this study examines the mediating role of customer satisfaction in the relationship between CRM and corporate image with customer loyalty. The mediating analysis provides insights into the mechanisms by which these variables interact, highlighting the pivotal role of satisfaction in fostering stronger customer relationships and long-term loyalty. This comprehensive approach enriches the understanding of strategic pathways for enhancing customer retention and contributes to the broader discourse on sustainable competitive advantage in the electricity service sector.